Tire pressure measurement using a SAW hybrid sensor - Schimetta, Gernot; Dollinger, Franz; Weigel, Robert (XVI IMEKO (International Measurement Confederation) World Congress, 2000)
A tire pressure measuring system based on surface acoustic wave (SAW) sensors is presented. Since SAW sensors are powered by the energy of the RF field no battery is required, which is a major drawback of conventional systems. A successful combination of a SAW reflective delay line with a capacitive pressure sensor is shown. With a new way of matching the sensor impedance to the SAW reflector impedance both a high signal-to-noise ratio and a high signal dynamic are achieved which supports accurate signal evaluation. A prototype of a tire pressure sensor unit is presented.
elib2cris::1512001600,schimetta2000b
Keywords: SAW; trie pressure sensor; wireless remote sensing